Caracterización de los residuos sólidos urbanos del botadero municipal de Quisaloma y el efecto que genera al lixiviado en el estero "Cerrito. - Manobanda Lara, Karla Dayana (2016)
The investigation was carried out in the Quinsaloma canton, Los Ríos Province and was executed in the Cerritos enclosure, in the Cerrito estuary. Samples were taken in the central sector 25 and in the periphery 20 for the characterization of the RSU, in the results of the weighing of each sample were compared with the typical values of humidity proposed by Tchobanoglous (2005); It was then classified into three degradation groups: slow, rapid and other values; Finally, the amount of leachate present in the dump and its effect on the affluent of the "Cerrito" estuary. In the results, the MSW were characterized in two sampling sites (center and periphery) generating 9.35 and 9.78 k / week in their respective order; Degradation is set at the center, slow 7.18 K / week, rapid 16.72 K / week and other waste 4.13 K / week; For the periphery the waste is slow 6.93 K / week, fast 15.45 K / week and other waste 6.96 K / week. Generation per capita 0.83 center and 0.80 kg / day periphery, obtaining on average 0.816 kg / day in both sites sampled. The actual water content (dm3) of MSW per capita in total of 0.16 dm3 per day among all MSW. The amount of leachate generated has a production ceiling in March with 4168.7 mm; The physical and chemical characteristics of the leachate in the tributary were 3.9 OD / l and could cause hypoxia with the disappearance of sensitive organisms and species. The parameters DBO5, Fecal Coliforms, Total Coliforms, Zinc, Copper and Iron exceed the TULSMA Regulations Ministerial Agreement 097 A.